Habilidades sociais e bem-estar subjetivo de crianças dotadas e talentosas - França, Maria Luiza Pontes de (Universidade Federal de São Carlos, 2012)
In considering the national publications about gifted and talented children, it was noticed that there is a lack on scientific knowledge and empirical research about the socio-emotional characteristics of these children, specifically, about social skills repertoire and the level of subjective well-being. It was noticed too, that there is a prevalence of publications on cognitive characteristics and educational needs of these children. Therefore, the main objectives of this study were: (1) characterize the repertoire of social skills in gifted and talented children; (2) characterize the level of subject well-being in gifted and talented children; (3) investigate the relationship between social skills and subjective well-being of these children; (4) identify the predictive power of social skills in explaining subjective wellbeing of these children; (5) identify possible differences and similarities in relation to social skills classes in different domains of gifted (general intelligence, creativity, socio-emotional and sensorimotor); and (6) identify possible differences and similarities in relation to subjective well-being in different domains of gifted (general intelligence, creativity, socioemotional and sensorimotor). Sample was composed by 394 children with age range between eight and twelve years. They were separated in 269 gifted and talented children and 125 not gifted children. Participants completed the following questionnaires: Evaluation System of Social Skills (ESSS), Multidimensional Scale of Life Satisfaction for Children (MSLSC), Scale Positive and Negative Affect Children and Socio-Demographic Questions. Descriptive and inferential analyzes were performed in order to accomplish the aims of this research. Results showed that gifted children reported a broader social skills repertoire and a higher level of subjective well-being than non-gifted children. Regarding the classes of social skills and the subjective well-being indicators, both samples of children reported more frequently the expression of positive feelings and higher satisfaction with family and reported a lower frequency of problem avoidance and lower level of negative affect. These results indicated that a broader repertoire of social skills is associated with a higher level of subjective wellbeing in gifted and talented children. Subjective well-being was predicted by most social skills classes. It was observed that when compared gifted children in a domain with gifted children who did not showed the same performance in that domain were observed differences in some social skills classes and in some subjective well-being indicators for verbal and mathematical sub-domains (belonging to general intelligence domain) and for socioemotional and sensorimotor domains. In conclusion, this study can be considered relevant for the scientific literature of this field research. The results demonstrate that the socio-emotional disadjustment seen as a gifted and talented children feature is a myth, once these children reported a broader social skills repertoire and higher level of subjective well-being overall. Moreover, information about the social skills repertoire and the level of subjective well-being of gifted and talented children might contribute to identify children who excel in the socioemotional domain, once there is a few programs that select gifted children based on their social competence and related variables.
Social skills and subject well-being of gifted and talented children
Keywords: Habilidades sociais em crianças; Bem-estar subjetivo; Dotação; Talentos; Social skills; Subject well-being; Giftedness; Talent; CIENCIAS HUMANAS::PSICOLOGIA